Revisiting politicization: Political advisers and public servants in Westminster systems - Eichbaum C; Shaw RH (Wiley Periodicals, 2008)
In recent times much has been made of the threat some argue is posed by political advisers to the impartiality of the Westminster civil service. Drawing on survey of senior New Zealand civil servants, this article examines the degree to which political advisers are perceived as a threat to civil service neutrality and describes the form taken by that threat as variously perceived. On the evidence reported, it is suggested that traditional understandings of "politicization" need to be reconceptualized if they are to fully account for the nature of the relationship between political and civil service advisers. To existing conceptions of politicization, therefore, the article proposes adding another: "administrative politicization," allowing for different gradations of politicization to be identified, and enabling a nuanced assessment of the nature and extent of a risk to civil service neutrality that, the data suggest, is not as great as is sometimes alleged. © 2008 Wiley Periodicals, Inc.
Keywords: 1605 Policy and Administration; 1606 Political Science; 1899 Other Law and Legal Studies